Safety of exercise training in multiple sclerosis: a protocol for an updated systematic review and meta-analysis - Learmonth, Y.C.; Pilutti, L.A.; Herring, M.P.; Motl, R.W.; Chan, Bryan; Metse, A.P. (2021)
Background: There has been an exponential growth in the number of clinical research studies regarding exercise training in multiple sclerosis, and literature reviews and meta-analyses have documented the many benefits of exercise training. This research further requires careful review for documenting the safety of exercise training in multiple sclerosis, as clarity on safety represents a major hurdle in the clinical prescription of exercise behaviour.